Democratisation in South Korea and Taiwan : the effect of social division on inter-Korean and cross-strait relations - Chung, Chien Peng (2009)
My paper highlights a central element that is oftened overlooked in studies on South Korea's policies toward North Korea and Taiwan's relations with mainland China: the profound effect on inter-Korean and cross-Strait ties brought about by the political evolution of Seoul and Taipei in the last 15 years from authoritarianism to democracy. Democratisation exacerbates social division within a country, as a result of which relations with foreign countries get ameliorated or aggravated, depending on the revealed preference of the median voter. Democratic transition and consolidation in South Korea and Taiwan have undoubtedly furthered the policisation of foreign and security issues, by opening up the political space which allows for their articulation, and widening the spectrum of ideological debate to include "ethnic" and "class" issues, which in turn affected public sympathies for intercourse with Pyongyang and Beijing respectively.